«АЙДОС БИЙ» ДӘСТАНЛАРЫНДА ТАРИЙХЫЙ ЎАҚЫЯЛАРДЫҢ ҲӘМ ТАРИЙХЫЙ ТУЛҒАЛАРДЫҢ СӘЎЛЕЛЕНИЎИ - Тоқымбетова, Г.А. (FAN va JAMIYAT, 2017)
The article analyzes the problems of transformation of historical truth into artistic truth in Berdakh’s epos “Aidos Biy”and the process of creative search of the author in creating the images of historical figures. It also reveals Berdakh’s unique original skill in depicting the historical theme.